العقل في الإسلام: منزلته، ومجالاته، وعلاقته بالنقل - Hammad Mohammed Yusuf (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aims to clarify the position of reason and its domain in Islam in view of the texts of the Qur'an and Sunnah, and to outline the concept of the relationship of reason and naql saḥīḥ, by examining the